Dilatometric Effects Accompanying Phase Transformations during Tempering of Spring Steels - Kotous, Jakub; Nový, Zbyšek; Motyčka, Petr; Salvetr, Pavel (Manufacturing Technology Journal, 2024)
The tempering procedure of quenched 54SiCr6 spring steel was analyzed using continuous heating dilatometry, isothermal dilatometry, metallography, and hardness measurement. The dilatometry was performed on four different steel modifications with graduated Si content and with two levels of Cu. Metallography and hardness measurement were analyzed only on samples with one Si level. Two types of tempering procedures were compared in this experimental program. The first one was sim-ple one-step tempering, the other was a special procedure of strain assisted tempering (SAT), which includes double tempering and strain applications between tempering. A dilatometry analysis with the support of metallography contributes to the material behaviour explanation, which is considerably different in both processing cases.
Keywords: Dilatometry; Strain assisted tempering; Nano-twins; Spring steel